Glacial Deposits of South-Central Fayette County, Ohio - Johnson II, Harold Everett (The Ohio State University, 2005)
Glacial deposits are common and varied across Ohio. These deposits chiefly include lodgment till, ablation till, and outwash. All of these sediment types can be found by drilling into the subsurface of Fayette County, Ohio. The study region, located in the south-central portion of Fayette County (along Miami Trace Road), was examined for glacial deposits using data collected from water well logs and drilling reports. Additional data sources including topographic maps, open-file bedrock geology maps, and open-file bedrock topography maps were used and a cross-section constructed. Variations in bedrock topography record effects of the Teays Stage drainage and the Deep Stage drainage, which in turn influences the thickness of drift. The overlying glacial sediments consistently show an upward pattern of hardpan, sand, and oxidized clay loam in both the ground moraine and end moraine landforms. This sequence is interpreted to record a glacial advance, an increase in meltwater, and the deposition of the uppermost layer either from supraglacial/englacial debris or by a second advance of the Wisconsinan ice sheet. No embargo